Determinants of Individual Taxpayer Compliance Based on NPWP Ownership Obligations, Taxation Understanding, and Taxpayer Awareness - Yuliatiningsih, Dwi; Priono, Hero (Gorontalo Accounting Journal, 2026)
This study aims to analyze the effect of Taxpayer Identification Number (NPWP) ownership requirements, taxation understanding, and taxpayer awareness on individual taxpayer compliance at the Surabaya Rungkut Tax Office. Data collection was conducted through questionnaires administered to one hundred respondents, then analyzed using partial least squares structural equation modeling techniques, which included reliability and validity tests, structural model evaluation, and hypothesis testing. The results showed that the obligation to have a Taxpayer Identification Number had a positive and significant effect on individual taxpayer compliance. Tax understanding was also found to have a positive and significant effect on improving the accuracy of reporting and fulfillment of tax obligations. In addition, taxpayer awareness of the function and role of taxes in national development also had a positive and significant effect on the level of compliance. These findings confirm that taxpayer compliance in the research area is influenced by administrative factors, knowledge, and internal awareness, which mutually reinforce compliant behavior in fulfilling tax obligations.